Biopharmaceuticals protection, cure and the real winner - Mohd Lila, Mohd Azmi (Universiti Putra Malaysia Press, 2011)
Conventionally, product development and manufacturing of pharmaceuticals are based on small molecules and simple chemical processes. Then at the end of the genomic era, the industry was forced to adopt sophisticated biotech-based approaches for innovation of new kinds of pharmaceutical products, termed biopharmaceuticals. Following the industrial transformation, anti-cancer therapy, therapeutic proteins, vaccines and hormone therapy become the major outputs. Specific biopharmaceutical products include insulin for diabetes, erythropoietin (EPO) to treat neutropenia, granulocytes-colony stimulating factors (G-CSFs), growth hormones, and cytokines (for therapeutic purposes). Currently, monoclonal antibodies (mAbs) are the fastest growing therapeutic proteins in R&D and market globally; targeting at cancer treatment, inflammatory and immune related diseases. Existing cytotoxic drugs have been rejuvenated via conjugation technology with MAbs to improve effects of the former. Lead by mAbs, therapeutic protein market has claimed at least 30% of the total value of biopharmaceuticals in the global market. Cytokines is already in advanced development for treatments of cancers, benign prostatic hyperplasia, gout and inflammatory conditions. Interestingly, insulin has been in the market for a long time, but R&D efforts are still strong especially on new formulation and delivery of oral or other non-invasive dosage. On the other hand, even though many vaccines are already well established in the market, new technologies are still needed to make those vaccines become more potent, cost effective and convenient. Previously, it was almost impossible to accelerate development of vaccines against some diseases as it was limited by technology. Currently, there are many new vaccines against existing targets and vaccines against new targets in the pipeline. Despite numbers of failures in the past, many biopharmaceutical companies are not discouraged to develop difficult vaccines against major problems or complex diseases including malaria, dengue, hepatitis C and HIV. Acute issues on diseases, for instance bio-terrorism, SARS and influenza, became a major growth driver for development of new vaccines and method of production. The cost of producing biopharmaceuticals is nowhere going to be cheap. The advancement of biopharmaceutical industry also stimulates “fringe industries” that supports the entire value chain, for example an improved bio-process technology, chromatography, bio-assay development, preclinical and clinical trials contract research organisation (CRO), sophisticated manufacturing technology, bioinformatics, contract manufacturing organisation (CMO), cold-chain management and logistics. From the business perspective, the requirement for highly specialised knowledge and skilled worker, great amount of funding required for investment and long-term investment horizon with a big loop in J-Curve serve as great barriers to new entrants. Despite the high risks, many sophisticated investors treated this as a great opportunity for potential higher returns from successful investee companies, provided that they are well equipped with the necessary bullets for evaluation, forecasting and making the right decision before joining the party.